(untitled) (Development Service Industry Management, 2024)
Modern business environment is characterized by high dynamism, which requires the adaptation of management strategies to global changes. Effective management of the growth and maturity stages of companies is critically important to ensure their sustainability and long-term development. A systematization of the main challenges faced by growing and mature companies has been conducted in the article. Based on the analysis of theoretical approaches and empirical research, tools for managing the lifecycle of growing and mature companies in the conditions of technological transformations and globalization have been formed. A special attention is paid to tools for risk monitoring, change management, and the implementation of modern technologies. The results of the research are based on the interdisciplinary approach and are aimed at improving the practice of company lifecycle management. The main conclusions contribute to the development of the company lifecycle theory, providing a theoretical and methodological basis for the development of adaptive strategies that integrate the principles of financial and economic security, sustainability, and innovative development. This allows companies not only to adapt to challenges but also to transform them into opportunities in a changing business environment. Particular attention is paid to the tools of risk monitoring, change management, and the implementation of modern technologies. The research results are based on an interdisciplinary approach and are aimed at improving the practice of company lifecycle management. The main conclusions contribute to the development of the company lifecycle theory, providing a theoretical and methodological basis for the development of adaptive strategies that integrate the principles of financial and economic security, sustainability, and innovative development. This allows companies not only to adapt to challenges but also to transform them into opportunities in a changing business environment.